libharpia: a New Cryptographic Library for Brazilian Elections - Pacheco, Rodrigo; Braga, Douglas; Passos, Iago; Araújo, Thiago; Lagrota, Vinícius; Coutinho, Murilo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2022: Anais do XXII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2022)
The Research and Development Center for Communication Security (CEPESC) has a long partnership history with the Brazilian Superior Electoral Court to improve the security of the Brazilian election system. Among all the contributions from CEPESC, probably the most important is a cryptographic library used in some critical moments during the election. In an effort to improve transparency and auditability of the solution, we present the new cryptographic library developed at CEPESC, named libharpia. Its main design goal is to allow transparency and readability while substantially increasing security. One of the main advances is the use of post-quantum cryptography, implemented through secure hybrid protocols that mix current cryptographic standards (specifically elliptic curves) with new cryptographic primitives based on Lattices, believed to be secure against quantum computers.